2013
DOI: 10.1152/jn.00414.2013
|View full text |Cite
|
Sign up to set email alerts
|

Multichannel brain recordings in behavingDrosophilareveal oscillatory activity and local coherence in response to sensory stimulation and circuit activation

Abstract: Multichannel brain recordings in behaving Drosophila reveal oscillatory activity and local coherence in response to sensory stimulation and circuit activation. J Neurophysiol 110: 1703-1721, 2013. First published July 17, 2013 doi:10.1152/jn.00414.2013.-Neural networks in vertebrates exhibit endogenous oscillations that have been associated with functions ranging from sensory processing to locomotion. It remains unclear whether oscillations may play a similar role in the insect brain. We describe a novel "who… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
55
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 36 publications
(60 citation statements)
references
References 68 publications
5
55
0
Order By: Relevance
“…2E), and the responses varied with brain region, as expected (26)(27)(28)(29). In general, flicker responses were of greater amplitude in the optic lobes than in the central brain (e.g., mushroom body) (Fig.…”
Section: Significancesupporting
confidence: 63%
“…2E), and the responses varied with brain region, as expected (26)(27)(28)(29). In general, flicker responses were of greater amplitude in the optic lobes than in the central brain (e.g., mushroom body) (Fig.…”
Section: Significancesupporting
confidence: 63%
“…C , Example of pre-processed LFPs data before anesthesia (0% isoflurane) from one fly. A standardized fly brain is shown for comparison (Paulk et al, 2013b, 2015). The electrode contacts are indicated by white dots (not to scale).…”
Section: Methodsmentioning
confidence: 99%
“…Previous work has shown that the fly heartbeat can manifest as low-frequency (2–4 Hz) oscillatory activity in central channels (Paulk et al, 2013b; Yap et al, 2017). Heartbeats are unlikely to affect the results presented here because we use bipolar rereferencing which eliminates common input to neighboring channels, as may be expected from a muscle artifact (Cohen and Tsuchiya, 2017).…”
Section: Methodsmentioning
confidence: 99%
“…Tethered flies were positioned above a 45.5 mg air-supported Styrofoam ball (Fig. 1 a , b ), similar to that described by Paulk et al (2013).…”
Section: Methodsmentioning
confidence: 99%
“…We used a recently developed multielectrode preparation (Paulk et al, 2013) to record evoked local field potentials (LFPs) across the fly brain in response to flickering visual stimuli. The flickering stimuli produced a periodic response, known as steady-state visually evoked potentials (SSVEPs; Norcia et al, 2015), that allowed us to accurately track the responses in the frequency domain across brain structures, from the optic lobes to the central brain.…”
Section: Introductionmentioning
confidence: 99%